THE IMPLEMENTATION OF REGULATIONS IN HANDLING COVID-19 IN INDONESIA - sukirno sukirno (Universitas 17 Agustus 1945 Semarang, 2021)
This study aims to describe how the regulations in handling Covid -19 occur in Indonesia and their implementation. This study uses a normative juridical research method, which is a study that tries to examine the laws and regulations used in handling Covid -19 in Indonesia. The study results show several regulations in handling Covid-19 at the moment, both at the national and regional levels, such as the Law of the Republic of Indonesia Number 6 of 2018 concerning Health Quarantine to other implementing regulations. However, in practice, the implementation has not run optimally. There are still many violators in the community, and this is because the existing regulations do not regulate strict sanctions for violators. So that regulations governing the application of law in handling Covid -19 in Indonesia still need reforms in the field of law, with the aim that the law can be felt by the community, namely legal certainty, justice, and benefits for the community.